Influence of the flood pulse on mercury accumulation in detritivorous, herbivorous and omnivorous fish in Brazilian Amazonia - Azevedo, Lucas Silva (Ecotoxicology (London, England), 2019)
Hg accumulation in fish is influenced by several factors including seasonality. In the Amazon, ecosystems are marked by strong seasonal variation in precipitation, which leads to drastic changes in the water level of lakes and rivers. The aim of this study was to evaluate Hg levels in muscle of detritivorous, herbivorous and omnivorous fish from an Amazon lake (Madeira River Basin, Amazonas, Brazil) over four seasons (rising water, high water, falling water and low water). We hypothesized that total Hg concentration varies during the seasons. The results indicate that total Hg levels in detritivorous fish were higher in rising and low water seasons while in herbivorous and omnivorous fish the total Hg concentration was higher during the rising water season. The hypothesis was supported by the results. Additionally, the study provides evidence that Hg levels in fish with different feeding habits are influenced by the flood pulse of the Amazon region